HETEROSIS FOR TUBER YIELD AND ITS COMPONENTS IN POTATO - Patel, V P; Patel, P S; Patel, N H (Potato Journal, 2013)
In a line x tester (7 x 4) study, degree of heterosis varied from cross to cross for all the traits.The highest relative heterosis for tuber yield was observed in the progeny of Kufri Lauvkar x DP-9904(35.15%). None of the progenies exhibited significant positive heterobeltiosis for tuber yield per plant whereas thirteen progenies showed significant positive heterobeltiosis for number of tuber per plant. High heterosis was observed for number of tubers per plant and number of leaves per plant. While, low heterosis values were observed for tuber yield per plant, average weight of tubers, harvest index and number of stems per plant; moderate heterosis was observed for days to maturity, plant height, fresh weight of tops per plant and dry matter content. Over all, frequency of heterotic crosses was higher among the crosses involving parents with average x average gca effects.